2023
DOI: 10.5194/acp-23-4685-2023
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent structure of the Arctic boundary layer in early summer driven by stability, wind shear and cloud-top radiative cooling: ACLOUD airborne observations

Abstract: Abstract. Clouds are assumed to play an important role in the Arctic amplification process. This motivated a detailed investigation of cloud processes, including radiative and turbulent fluxes. Data from the aircraft campaign ACLOUD were analyzed with a focus on the mean and turbulent structure of the cloudy boundary layer over the Fram Strait marginal sea ice zone in late spring and early summer 2017. Vertical profiles of turbulence moments are presented from contrasting atmospheric boundary layers (ABLs) fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Part of this variation is likely driven by differences in the mean-state wind shear amongst the models. We would expect an increase in wind-driven atmospheric turbulent heat fluxes with stronger wind shear (Chechin et al, 2023), and as a result, a stronger suppression of low-level stability. This relationship is seen (not shown) in the NP station data, for which there is a positive correlation (significant at 90% confidence) between the mean-state wind shear at a particular station, and the reduction in stability with wind speed recorded at that station.…”
Section: Other Controls On Low-level Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this variation is likely driven by differences in the mean-state wind shear amongst the models. We would expect an increase in wind-driven atmospheric turbulent heat fluxes with stronger wind shear (Chechin et al, 2023), and as a result, a stronger suppression of low-level stability. This relationship is seen (not shown) in the NP station data, for which there is a positive correlation (significant at 90% confidence) between the mean-state wind shear at a particular station, and the reduction in stability with wind speed recorded at that station.…”
Section: Other Controls On Low-level Stabilitymentioning
confidence: 99%
“…Higher near-surface wind speeds are associated with increased near-surface air temperature and a reduction in the strength of near-surface temperature inversions over Arctic sea-ice (Chechin et al, 2019;Wiel et al, 2017). Additionally, wind shear is an important control on low-level atmospheric turbulent heat fluxes in the polar night (Chechin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of turbulence in the PBL has been previously recognized to be closely associated with atmospheric stability (Chechin et al, 2023;Chen et al, 2013;Lai et al, 2021;Muhsin et al, 2016). Therefore, we take the gradient Richardson number (𝑅𝑖) as a variable to characterize atmospheric stability and the formation of turbulence over the TP.…”
Section: Calculation Of the Gradient Richardson Numbermentioning
confidence: 99%
“…A vast range of previous studies have attempted to figure out the mechanisms behind the observed turbulence, but most of them are based on radiosonde measurements or model simulation or reanalysis data (e.g., Banerjee et al, 2018;Che and Zhao, 2021;Wang et al, 2023a). A myriad of driving mechanisms is proposed to account for the PBL development over the TP, such as surface thermal and dynamic forcing, atmosphere stability, among others (Chechin et al, 2023;Chen et al, 2016;Lai et al, 2021;Wang et al, 2023a;Wang and Zhang, 2022). It has been demonstrated that the buoyancy term contribution on the southern slope of the TP is significantly larger than that on the southeastern edge of the TP (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of near-surface wind speed can be used to infer mechanical production of turbulence (Banta, 2008). Radiatively influenced processes impacting the Arctic ABL include the generation of buoyant turbulence through surface energy fluxes emitted from open-water regions such as leads (Lüpkes et al, 2008); cold-air advection, especially over thin ice (Vihma et al, 2005); enhanced downwelling longwave radiation from low-level clouds (Wang et al, 2001); or turbulent mixing within the clouds and below cloud base due to cloud-top radiative cooling (Tjernström et al, 2004;Chechin et al, 2023). Measurements of the surface radiation budget and cloud characteristics support an understanding of the possibility for radiatively generated turbulence in the ABL.…”
Section: Introductionmentioning
confidence: 99%